2012
DOI: 10.1515/znc-2012-11-1201
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Constituents from Alchemilla vulgaris L. and Alchemilla mollis (Buser) Rothm. at Different Dates of Harvest

Abstract: Acetone/water extracts from the leaves, including stalks, of Alchemilla vulgaris L. and A. mollis (Buser) Rothm. were investigated for their phenolic composition by liquid chromatography- tandem mass spectrometry (LC-MS/MS). A total of 24 and 27 compounds were detected for A. vulgaris and A. mollis, respectively. Pedunculagin and agrimoniin, as described in earlier reports for A. vulgaris, as well as other monomeric and oligomeric ellagitannins such as sanguiin H-10, castalagin/vescalagin, and galloyl-bis-hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…A similar phenomenon was observed for the genus Alchemilla . In A. vulgaris and A. mollis the content of agrimoniin ( 36 ) increased by the end of the mass flowering period by more than 100% [ 77 ]. The presence of potentillin ( 32 ) in all seasonal samples is probably because it is a main intermediate metabolite in the production of agrimoniin.…”
Section: Resultsmentioning
confidence: 99%
“…A similar phenomenon was observed for the genus Alchemilla . In A. vulgaris and A. mollis the content of agrimoniin ( 36 ) increased by the end of the mass flowering period by more than 100% [ 77 ]. The presence of potentillin ( 32 ) in all seasonal samples is probably because it is a main intermediate metabolite in the production of agrimoniin.…”
Section: Resultsmentioning
confidence: 99%
“…The health-benets of this phenol acid is correlated to several health benets including antioxidant, anticancer, antimutagenic, anti-diabetic effects. 29,30 Duckstein et al 31 have detected in Alchemilla vulgaris extracts a signicant concentration of phenolic acids, such as chlorogenic, gallic, ellagic acids in lower concentrations. Besides phenolic acids, the avonoids catechin, and quercetin were recorded in signicant concentration in EA extract, where catechin was the most dominant (8144.98 mg g À1 ).…”
Section: Lc-ms/ms Characterization Of Phenolic Compoundsmentioning
confidence: 99%
“…A plenty of studies supported various health benets. This phenolic compound is reputable as one of the most powerful antioxidant, 31,32 while several studies have shown the a strong connection between catechin and inhibition of cancerogenesis, such like suppression on breast and ovarian cancer cell growth. 33,34 Flavonoid glucosides were identied in all tested extracts, and generally their concentration were the most abundant in EA extract.…”
Section: Lc-ms/ms Characterization Of Phenolic Compoundsmentioning
confidence: 99%
“…By using liquid chromatography-tandem mass spectrometry technique, monomeric and oligomeric ellagitannins were identified in acetone/water extracts obtained from the leaves of A. mollis (Duckstein et al, 2012). In our previous study, hyperoside and isoquercetin quantification in aqueous methanolic extracts of A. mollis and A. persica was conducted by HPLC.…”
Section: Discussionmentioning
confidence: 99%